Pro-Kontra dan Prospektif Kewenangan Uji Konstitusionalitas Perpu - Iskandar Muda (The Constitutional Court of the Republic of Indonesia, 2016)
Pros and cons of the authority to deal with judicial constitutionality review of Government Regulation in Lieu of Law (Perpu) either from fellow judges of the Constitutional Court (MK) or from the world of legal science is acceptable. The pros and cons is not due to the differences in interests between them, but it is caused by the differences in schools or schools of thought and interpretation methodologies adopted. The authority of the Constitutional Court to review the constitutionality of Perpu is in line with the philosophy of Judicial Activism (the concept of active understanding) which is identical to the